2017
DOI: 10.1097/md.0000000000008684
|View full text |Cite|
|
Sign up to set email alerts
|

Primary extraskeletal myxoid chondrosarcoma in cerebellum

Abstract: Rationale:Extraskeletal myxoid chondrosarcoma (EMC) is a rare malignant neoplasm of which intracranial EMC is the rarest.Patient concerns:We present an unusual case report of a 41-year-old woman who was sent to the emergency department for a sudden headache and other symptoms related to increased intracranial pressure.Interventions:Emergent CT revealed an occupying lesion in the left cerebellum with surrounding edema. A complete surgical excision of the lesion through a transcortical approach was performed. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Our demographic analysis of locoregional myxoid leiomyosarcomas showed that most patients were older than 50 compared with locoregional myxoid liposarcomas, and locoregional myxoid chondrosarcoma patients were showing no big difference between age variables according to data reported by SEER, and these results are similar to that reported in literature revealing that myxoid leiomyosarcomas occurred mostly in the elderly [ 44 – 46 ]. Myxoid liposarcoma and myxoid chondrosarcoma tumors with locoregional metastasis have mostly male predilection [ 44 , 47 , 48 ], and the locoregional myxoid leiomyosarcoma tumor has commonly female predilection [ 49 ]. Our obtained data indicated that cases of myxoid liposarcomas and myxoid chondrosarcomas with locoregional metastasis were mostly male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our demographic analysis of locoregional myxoid leiomyosarcomas showed that most patients were older than 50 compared with locoregional myxoid liposarcomas, and locoregional myxoid chondrosarcoma patients were showing no big difference between age variables according to data reported by SEER, and these results are similar to that reported in literature revealing that myxoid leiomyosarcomas occurred mostly in the elderly [ 44 – 46 ]. Myxoid liposarcoma and myxoid chondrosarcoma tumors with locoregional metastasis have mostly male predilection [ 44 , 47 , 48 ], and the locoregional myxoid leiomyosarcoma tumor has commonly female predilection [ 49 ]. Our obtained data indicated that cases of myxoid liposarcomas and myxoid chondrosarcomas with locoregional metastasis were mostly male patients.…”
Section: Discussionmentioning
confidence: 99%
“…IHC panel of markers such as vimentin, cytokeratin, S100 and GFAP play a vital role in histopathological diagnosis. Vimentin positivity and cytokeratin negativity were reported in most cases of primary intracranial EMC in literature [14,17,18,21]. S100 negativity helps to rule out chordoma [34].…”
Section: Discussionmentioning
confidence: 97%
“…Over past 28 years, since the first description of myxoid chondrosarcoma in 1972, there are only 17 cases of intracranial extra-skeletal myxoid chondrosarcoma (EMC) reported in literature. The intracranial sites of origin were cerebellopontine angle, cerebellum, dura, fourth ventricle, pineal gland, falx cerebri and brain parenchyma [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Among the reported cases, there was only one case of intraventricular origin, which originated from fourth ventricle [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the current case can rule out chordoma. EMC is an extremely rare malignant tumor showing malignant chondroblast-like cells in a background of myxoid matrix 20. It is characterized by hypocellular myxoid nodules separated by fibrous septa of variable thicknesses;21 immunohistochemistry is positive for vimentin and synaptophysin and negative for S-100 and EMA.…”
Section: Discussionmentioning
confidence: 99%